Measuring Future Selves in Second Language Learning Motivation in Collectivist Cultures: Case Study From Saudi Arabia - Danya Shaalan (SAGE Open)
The second-language (L2) Motivational Self System (L2MSS) proposed by Zoltán Dörnyei described how L2 learners are motivated through envisioning their ideal future L2 self. The L2MSS framework for studying L2 motivation has had mixed results. The aim of this study was to evaluate measuring future selves as L2 motivators consistent with the L2MSS in Saudi female college students enrolled in a higher education English language program, and consider how these findings are applicable to collectivist cultures. A 20-item instrument was developed that showed evidence of validity and reliability in measuring ideal L2 future self and two ought-to ideal future selves as sources of L2 motivation. However, given the collectivist nature of Saudi culture, these measurements were positively correlated, giving rise to the question as to the utility of such a measurement. Future research on further validating the instrument and exploring ways to increase L2 motivation among learners in collectivist cultures is discussed.